Long-range action of Wingless organizes the dorsal-ventral axis of the Drosophila wing. - Neumann, C.J.; Cohen, S.M. (Development, 1997)
Short-range interaction between dorsal and ventral (D and V) cells establishes an organizing center at the DV compartment boundary that controls growth and specifies cell fate along the dorsal-ventral axis of the Drosophila wing. The secreted signaling molecule Wingless (Wg) is expressed by cells at the DV compartment boundary and has been implicated in mediating its long-range patterning activities. Here we show that Wg acts directly, at long range, to define the expression domains of its target genes, Distal-less and vestigial. Expression of the Achaete-scute genes, Distal-less and vestigial at different distances from the DV boundary is controlled by Wg in a concentration-dependent manner. We propose that Wg acts as a morphogen in patterning the D/V axis of the wing.